Cyanobacterial Akinete Distribution, Viability, and Cyanotoxin Records in Sediment Archives From the Northern Baltic Sea - Wood, Steffaney M.; Kremp, Anke; Savela, Henna; Akter, Sultana; Vartti, Vesa-Pekka; Saarni, Saija; Suikkanen, Sanna (Frontiers in Microbiology, 2021)
Cyanobacteria of the order Nostocales, including Baltic Sea bloom-forming taxa Nodularia spumigena, Aphanizomenon flosaquae, and Dolichospermum spp., produce resting stages, known as akinetes, under unfavorable conditions. These akinetes can persist in the sediment and germinate if favorable conditions return, simultaneously representing past blooms and possibly contributing to future bloom formation. The present study characterized cyanobacterial akinete survival, germination, and potential cyanotoxin production in brackish water sediment archives from coastal and open Gulf of Finland in order to understand recent bloom expansion, akinete persistence, and cyanobacteria life cycles in the northern Baltic Sea. Results showed that cyanobacterial akinetes can persist in and germinate from Northern Baltic Sea sediment up to >40 and >400 years old, at coastal and open-sea locations respectively. Akinete abundance and viability decreased with age and depth of vertical sediment layers. The detection of potential microcystin and nodularin production from akinetes was minimal and restricted to the surface sediment layers. Phylogenetic analysis of culturable cyanobacteria from the coastal sediment core indicated that most strains likely belonged to the benthic genus Anabaena. Potentially planktonic species of Dolichospermum could only be revived from the near-surface layers of the sediment, corresponding to an estimated age of 1-3 years. Results of germination experiments supported the notion that akinetes do not play an equally significant role in the life cycles of all bloom-forming cyanobacteria in the Baltic Sea. Overall, there was minimal congruence between akinete abundance, cyanotoxin concentration, and the presence of cyanotoxin biosynthetic genes in either sediment core. Further research is recommended to accurately detect and quantify akinetes and cyanotoxin genes from brackish water sediment samples in order to further describe species-specific benthic archives of cyanobacteria.